Analisis Total Quality Management dalam Sistem Agribisnis Sayuran di Kecamatan Konda Kabupaten Konawe Selatan - Harianti Harianti; Usman Rianse; La Ode Alwi (Universitas Halu Oleo, 2020)
The purpose of this study is to analyze the application of Total Quality Management (TQM) in the vegetable agribusiness system in the upstream subsystem, post harvest handling and processing subsystems, marketing subsystems and support services subsystems. The study was conducted in Konda Subdistrict, Konawe Selatan Regency from August to September 2019. Sampling was carried out by simple random sampling method with a total sample of 58 people. The data collected includes: the application of TQM in vegetable agribusiness. Data collection was carried out by interview, observation and documentation. The data analysis was conducted in a descriptive qualitative manner, and to measure the application of TQM, a Likert scale was used. The study results show that the highest index of TQM application is in the vegetable agribusiness system is found in the upstream subsystem, while the lowest is in the supporting services subsystem.Keywords: total quality management; vegetable agribusiness; Likert scale